Low pretreatment serum concentration of vitamin D at breast cancer diagnosis in postmenopausal women - Machado, Murilo Renato Matos [UNESP]; de Sousa Almeida-Filho, Benedito; De Luca Vespoli, Heloisa; Schmitt, Eneida Boteon; Nahas-Neto, Jorge; Nahas, Eliana A P (Wolters Kluwer, 2019)
OBJECTIVE: The aim of the study was to evaluate the rate of and risk factors for low pretreatment vitamin D (VitD) levels in postmenopausal breast cancer (BC) women, compared with postmenopausal women without BC. METHODS: A cross-sectional clinical study was conducted to compare 209 women with BC (case group) to 418 women without BC (control group), age range: 45 to 75 years. The case group consisted of women diagnosed with BC, amenorrhea ≥12 months, aged ≥45 years, without use of medication or clinical conditions that might interfere with VitD levels. The control group consisted of women with amenorrhea ≥12 months, aged ≥45 years, without BC. The groups were matched for age and time since menopause, at a case: control ratio of 1:2. Serum 25-hydroxyvitamin-D [25(OH)D] concentration was measured in all women 10 to 20 days after BC diagnosis and before the proposed treatment. Serum levels ≥30 ng/mL were defined as sufficient. The Student's t test or gamma distribution, χ test, and logistic regression (odds ratio, OR) were used for statistical analysis. RESULTS: The BC group had a higher body mass index (BMI) and higher percentage of obesity than the control group (57.4% vs 40.2%, P < 0.0001). In addition, rates of insufficient (20-29 ng/mL) and deficient (<20 ng/mL) 25(OH)D levels were higher in BC patients than in controls (55.6% vs 49.3%, P = 0.039 and 26.2% vs 20.3%, P = 0.018), respectively. In risk analysis (adjusted for age, time since menopause, and BMI), BC patients had a 1.5-fold higher risk of developing low VitD levels (OR = 1.52, 95% CI, 1.04-2.22, P = 0.029) than women without BC. CONCLUSIONS: Postmenopausal women had an increased risk of VitD deficiency at the time of BC diagnosis, associated with a higher rate of obesity, than women of the same age group without cancer.